MOBILE CONSTRUCTION MANAGEMENT APPS: IMPACTS ON REAL-TIME DECISION MAKING - Stein, Danilo Ramos (Revista Sistemática, 2023)
The construction industry has witnessed significant advancements through the adoption of mobile construction management applications such as Fieldwire, PlanGrid, and Buildertrend. These apps facilitate real-time data collection, task tracking, inspections, and reporting, enhancing communication between field teams and office personnel. This paper analyzes the impact of these mobile solutions on decision-making processes, productivity, safety management, and cost control. It highlights the benefits of cloud integration, data analytics, and emerging technologies like IoT and AI in further optimizing construction project outcomes. Challenges such as user adoption and connectivity issues are also discussed. Overall, mobile apps represent a transformative tool enabling faster, more informed decisions that improve project efficiency and stakeholder collaboration.